THE RELEVANCE OF SEYYED HOSSEIN NASR'S PERSPECTIVE SPIRITUALITY TO THE WORLD OF ISLAMIC EDUCATION - Khofifah, Bulgis (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The Relevance of Seyyed Hossein Nasr's Perspective Spirituality with the World of Islamic Education is important for study to find out how spirituality relates to the world of Islamic education, and provide some views to improve the world of Islamic education. Paying attention to all sides of the world of education in order to provide provisions that really help human life to face the challenges of an era that is increasingly rapidly developing.The research objectives are: 1. To find out how the values of spirituality from the perspective of Seyyed Hossein Nasr. 2. To find out the values of Islamic education from the perspective of Seyyed Hossein Nasr. 3. To find out the relevance of the spiritual values from the perspective of Seyyed Hossein Nasr with Islamic education.